Classical vs. unit area method in the evaluation of differential renal function in unilateral hydronephrosis - Kepenek, Ferat; Koc, Zehra Pinar; Orhan, Irfan; Balci, Tansel Ansal; Aydin, Funda; Gungor, Ahmet Firat; Tektas, Cihat (Walter de Gruyter Gmbh, 2015)
Background: There are some problematic results in determination of differential renal function (DRF) by means of Tc-99m DMSA renal scintigraphy in hydronephrotic kidneys. In this study the classical method (CM) and unit area methods (UAM) in the estimation of DRF in unilateral hydronephrosis before and after intervention were compared. Methods: Twenty patients (12 M, 8 F; mean: 42.6 +/- 18.5 years old) who were candidates for surgery or intervention because of unilateral hydronephrosis were the subjects of this study. All the patients were evaluated by Tc-99m DMSA scintigraphy before and 3-6 months after the intervention. In order to estimate DRF both CM and UAM (obtained by division of the counts including the kidney ROI to pixel of the same ROI) were performed. Bland-Altman analyses were performed in order to compare the DRF values obtained from both methods. Results: The agreement between CM and UAM was poor in the preoperative estimation, however, the agreement was good after the operation or intervention. Conclusions: In this study it seems that DRF estimation with CM in unilateral hydronephrosis might be problematic in the determination of surgery thus UAM might be introduced as the method of choice in the determination of DRF in unilateral hyronephrosis.
Keywords: differential renal function; DMSA; hydronephrosis; unit area